Family Centered Approaches to Stunting Prevention - Umar, Fadly (Journal of Health Literacy and Qualitative Research, 2021)
Stunting remains a pressing global health concern, affecting millions of children worldwide. This study explores the role of family-based interventions in stunting prevention, focusing on maternal education, paternal involvement, household food security, and culturally integrated nutrition programs. A systematic review was conducted, analyzing studies from PubMed, Scopus, and Google Scholar to identify effective strategies for reducing stunting prevalence. The findings indicate that maternal education significantly influences child nutrition, as higher literacy levels lead to improved feeding practices. Paternal involvement also plays a crucial role, with engaged fathers contributing to healthier dietary choices and improved child growth outcomes. Additionally, household food security is strongly associated with reduced stunting risk, highlighting the importance of sustainable food production methods such as urban farming. Community-based interventions that incorporate local cultural practices enhance program effectiveness and acceptance. Despite these promising strategies, challenges such as time constraints for caregivers, inconsistent nutritional knowledge, and cultural barriers hinder implementation. Addressing these issues requires multi-sectoral approaches that integrate education, healthcare, and technological innovations in nutrition awareness. This study underscores the need for family-centered policies, digital nutrition tools, and expanded community health initiatives. Future research should focus on evaluating the long-term impact of these interventions to develop more sustainable solutions for reducing stunting rates globally.